PERANAN LEMBAGA KEAGAMAAN LOKAL DALAM MELAHIRKAN DAN MENGAWAL FATWA KEAGAMAAN (Studi Terhadap Peran Majelis Ulama Nagari Guguak Tabek Sarojo Kecamatan IV Koto Kabupaten Agam) - Busyro - Busyro (Islam Realitas: Journal of Islamic and Social Studies, 2015)
Majelis Ulama Nagari (MUNA) Nagari Guguak Tabek Sarojo as local religious institution which is formed along with the shift from village administration to village government. The main responsibility which is administered by MUNA is to maintain the diversity of Muslim in order not to deviate from the rules of God. As a result, MUNA gives “fatwa” and watches “fatwa” which has been formed by officials religious institutions. From the research, it was found that MUNA Guguak Tabek Sarojo should have power in order to overcome all problems faced by most of religious community that was by doing ‘Mudzakarah” in order to give legal solution (fatwa); generally, MUNA Guguak Tabek Sarojo had followed the procedures in formed of religious rule (fatwa) which was started from question from the society or dorp, then discussed in mudzakarah and involved in discussion with religious leaders who were competence in their fields, and always kept up to the source of Islam, Al Quran, tradition, religious leader’s agreement, and Qiyas. The decision about religion will not be confused with custom and tradition admitted in a dorp. Majelis Ulama Nagari (MUNA) Nagari Guguak Tabek Sarojo sebagai lembaga agama setempat yang dibentuk bersama dengan pergeseran dari pemerintahan desa kepada pemerintah desa. Tanggung jawab utama yang dikelola oleh MUNA adalah untuk mempertahankan keragaman Muslim agar tidak menyimpang dari aturan Allah. Akibatnya, MUNA memberikan "fatwa" dan jam tangan "fatwa" yang telah dibentuk oleh pejabat lembaga-lembaga keagamaan. Dari hasil penelitian, ditemukan bahwa MUNA Guguak Tabek Sarojo harus memiliki kekuatan untuk mengatasi semua masalah yang dihadapi oleh sebagian besar komunitas agama yang dengan melakukan 'Mudzakarah "untuk memberikan solusi hukum (fatwa); umumnya, MUNA Guguak Tabek Sarojo mengikuti prosedur dalam membentuk pemerintahan agama (fatwa) yang dimulai dari pertanyaan dari masyarakat atau dorp, dibahas dalam mudzakarah dan terlibat dalam diskusi dengan para pemimpin agama yang kompetensi di bidangnya, dan selalu terus sampai ke sumber Islam, Al Quran, tradisi, kesepakatan pemimpin agama itu, dan Qiyas. Keputusan tentang agama tidak akan bingung dengan adat dan tradisi mengakui dalam sebuah dorp.